Biological evaluation of subgingivally placed direct resin composite materials - Frese, Cornelia; Krüger, Tanja; Staehle, Hans Jörg; Lux, Christopher J.; Erber, Ralf (Journal of oral science, 2018)
Placement of composite resin restorations in deep subgingival cavities can damage surrounding soft tissues. In addition, commonly used resin-based composites (RBCs) might interfere with wound healing and periodontal health. To clarify cellular interactions with RBCs, we used an MTT assay to investigate adhesion of primary human gingival fibroblasts and human osteoblasts (hFOB 1.19) on five RBC materials with and without surface modifications (alumina blasting with 50- or 110-μm Al2O3). In addition, high-performance liquid chromatography (HPLC) was used to determine release of resin monomers from RBCs after 1 h, 1 day, and 7 days. As compared with tissue culture plastics (the control), cellular adhesion was significantly lower (P < 0.001) for human gingival fibroblasts and osteoblasts. Only minor, nonsignificant differences between individual RBCs were identified. HPLC analyses identified the release of three bifunctional methacrylates bisphenol A glycerolate dimethacrylate, triethylene glycol dimethacrylate, and diurethane dimethacrylate from RBCs and showed that monomer release increased between 1 h and 1 day but remained low. The present findings suggest that surface adhesion in the subgingival area is limited for the tested RBCs. Although residual monomer release was low for all tested RBCs, it might be sufficient to adversely affect cell adhesion.